1997
DOI: 10.1007/bf03160577
|View full text |Cite
|
Sign up to set email alerts
|

The Riluzole Early Access Programme: descriptive analysis of 844 patients in France

Abstract: Recent controlled trials in outpatients with amyotrophic lateral sclerosis (ALS) indicate that riluzole prolongs tracheostomy-free survival. After 12 months' treatment, riluzole 50 mg, 100 mg and 200 mg daily reduced the risk of death or tracheostomy (relative to placebo) by 24%, 34% and 31%, respectively (by 28%, 43% and 43%, respectively, after adjustment for known prognostic factors). This survival advantage (6-9 patients require treatment with riluzole to avoid 1 death/tracheostomy annually) compares favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…8,20,26 A recent well-designed study by Armon et al 3 demonstrated the relationship between rate of estimated linear disease progression and survival. When their patients were divided into groups with faster or slower progression, a significant difference in survival was observed.…”
Section: Discussionmentioning
confidence: 98%
“…8,20,26 A recent well-designed study by Armon et al 3 demonstrated the relationship between rate of estimated linear disease progression and survival. When their patients were divided into groups with faster or slower progression, a significant difference in survival was observed.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of excitotoxicity has been shown by other reports (Plaitakis and Caroscio, 1987; Rothstein et al, 1992; Rothstein et al, 1990). In fact, the effective compounds for ALS, including riluzole (Lacomblez et al, 1996; Meininger et al, 1997) and ceftriaxone (Berry et al, 2013; Rothstein et al, 2005), inhibit glutamate signaling at the agonist and receptor level, respectively. However, these drugs may also block physiological or basal glutamate signaling, which may hamper the normal functioning of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Riluzole was able to effectively reduce ischemic neuronal damage in the spinal cord (Lang-Lazdunski et al, 1999), and prevent motoneuron death in vitro after exposure to glutamate agonists (Estevez et al, 1995). Moreover, clinical trials have proven that riluzole increased survival of a subset of amyotrophic lateral sclerosis (ALS) patients with bulbar onset, and it is one of the most promising drugs for the treatment of ALS (Bensimon et al, 1994;Gordon, 2005;Meininger et al, 1997). We have shown in our previous studies that systemic administration of riluzole in animals that had their lumbar ventral root avulsed and reimplanted prevented the death of motoneurons (Nó grá di and Vrbová , 2001), even if onset of treatment was delayed by 10 days (Nó grá di et al, 2007).…”
Section: Introductionmentioning
confidence: 99%